1998
DOI: 10.1021/jp973384x
|View full text |Cite
|
Sign up to set email alerts
|

Triplet State Z/E-Photoisomerizations of Polyenes:  A Comparison of ab Initio and Density Functional Methods

Abstract: In the search for less CPU-costly methods for study of triplet state Z/E-photoisomerization of olefins, Kohn−Sham density functional theory (DFT) has been tested on 1,3-butadiene (BD) and 1,3,5-hexatriene (HT). Computed T1 energies were compared to those from CASSCF, CASPT2, and spin-projected UMP4(SDTQ) calculations as well as experiments. For both molecules it is necessary that nonlocal gradient corrections are made to the exchange functional since usage of the local spindensity approximation for exchange in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 71 publications
(126 reference statements)
3
19
3
Order By: Relevance
“…26 The calculations employed density functional theory (DFT), a less-CPU-costly approach, that was recommended for such systems, after a critical evaluation of different theoretical methods for the calculation of triplet 1,3-diene and 1,3,5-hexatriene potential energy surfaces. 27 In all of the cases cited above, experiment and theory agree that photoisomerization in the lowest triplet state occurs as a consequence of decay from triplet conformers that are twisted (close to perpendicular) about the isomerizing bond. The twisted conformers ( 3 p for stilbene; 3 pt and 3 pc for the dienes) represent minima on the triplet potential energy surface.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…26 The calculations employed density functional theory (DFT), a less-CPU-costly approach, that was recommended for such systems, after a critical evaluation of different theoretical methods for the calculation of triplet 1,3-diene and 1,3,5-hexatriene potential energy surfaces. 27 In all of the cases cited above, experiment and theory agree that photoisomerization in the lowest triplet state occurs as a consequence of decay from triplet conformers that are twisted (close to perpendicular) about the isomerizing bond. The twisted conformers ( 3 p for stilbene; 3 pt and 3 pc for the dienes) represent minima on the triplet potential energy surface.…”
Section: Discussionmentioning
confidence: 85%
“…Pertinent to the research described here are the satisfactory theoretical predictions of the experimental relative energies and structures of conformers, isomers, and transition states for their interconversion in the ground and lowest triplet states for the stilbenes , and the 1,4-dimethyl- and 1,4-diaryl-1,3-butadienes . The calculations employed density functional theory (DFT), a less-CPU-costly approach, that was recommended for such systems, after a critical evaluation of different theoretical methods for the calculation of triplet 1,3-diene and 1,3,5-hexatriene potential energy surfaces . In all of the cases cited above, experiment and theory agree that photoisomerization in the lowest triplet state occurs as a consequence of decay from triplet conformers that are twisted (close to perpendicular) about the isomerizing bond.…”
Section: Discussionmentioning
confidence: 98%
“…For example, adiabatic relaxation gives rise to a central polaronic feature in the bright 1 1 B u state 65,69,75,76 , as well as two-soliton or four-soliton structures for the dark 2 1 A g state 54,56,65 . 2) For short polyenes ranging from ethylene to octatriene, studies of low-lying excited state relaxation pathways suggest that non-planar molecular conformations are important at energy crossings [79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95] . This opens up the question of the nature of energy crossings and their associated geometries in the excited states of longer polyenes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a nonresonant multphoton ionization experiment has demonstrated that trans → cis isomerization of butadiene proceeds within about 420 fs . Theoretical approaches attempt to provide a detailed knowledge of the potential energy surfaces of the ground and electronically excited states as a tool for understanding the isomerization reaction paths. Semiclassical molecular dynamics calculations have been frequently used to study the photoisomerization dynamics of polyenes. Some early calculations were based on a one-dimensional approximation (torsion mode only). , These calculations provide a fairly comprehensive picture of the role of the C−C single bond but are unable to fully reveal the detailed mechanisms and irreversible nature of the reaction.…”
Section: Introductionmentioning
confidence: 99%